The role of lipid traits in mediating the effect of body mass index on serum urate - Peng, Liuqing; Jing, Jiarui; He, Simin; Wang, Juping; Gao, Xue; Wang, Tong (Frontiers in Endocrinology, 2022)
Objective: Explore whether total cholesterol (TC), high density lipoprotein(HDL), low density lipoprotein(LDL) and triglyceride(TG) are the mediators in the pathway of body mass index(BMI) on serum urate and determine proportion of the mediation effect. Methods: This study used observational and two-sample Mendelian Randomization(MR) analysis to explore the mediation effects of TC, HDL, LDL, and TG in the pathway of BMI on serum urate. We determined the size and the extent to which these lipids mediate any effect of BMI on serum urate. Results: Observational analysis results showed that HDL and TG can partially explain the association of BMI on serum urate, and the proportion of mediation effect was 10.2% and 8.9%, respectively. MR results demonstrated that TG has causal effect on serum urate (β = 0.22, 95%CI: 0.15, 0.29; p=2.28×10^(-10)) and its proportion of mediation effect was 14.1%. TC, HDL and LDL are not the mediators in the pathway of BMI to serum urate in MR estimates. Conclusion: To a certain extent, TG mediate the effect of BMI on serum urate, and the risk of gout may be reduced by controlling both BMI and TG.